Contribution of the component and thickness in acoustic performance of wall partitions - Andrade, Fábia Kamilly Gomes de (Universidade Estadual de Campinas, 2018)
The performance of the buildings has become a growing concern of the builders, considering the demands of the users and the competitiveness of the real estate market; besides the Brazilian norm of performance of residential buildings. As one of these requirements, one can cite the sound insulation of vertical fences, which cause acoustic discomfort when deficient. The objective of the present work is to evaluate the compliance of the internal and external walls in the field concerning the criteria established by the Brazilian performance standard, analyzing the results obtained to the type of component and the total thickness and the coating. For this, data were collected in 15 multi-floor buildings, which used the following components: ceramic brick, ceramic block, concrete block or gypsum block. It was found that only 25% of the components comply with the standard for internal vertical seals. For external vertical seals, only 10% of the evaluated components comply with noise class II criteria and none with noise class III criteria. It was also verified that the concrete block presents a better performance for internal and external walls, due to its more constant behavior in the frequency range of 100 to 3150 Hz. The total and coating thicknesses that corresponded to the best acoustic performance, obtained in the sampling, were also identified.